A discussion on methods of monetary analysis and norms for monetary policy - Bos, Hendricus Cornelis ([Rotterdam] : Rotterdam University Press, 1965)
This book is an attempt to summarize the discussion on monetary problems. It considered the methods of monetary analysis and norms for monetary policy.
Bibliography: p. 51-52.
usc 23/06/2017
Loans
Keywords: Inflation (Finance); Currency question